Analysis of sucralose by high performance liquid chromatography in diet soft drink and table top sweetener - Kimura, Iracema de Albuquerque (2005)
Sucralose is derived from sucrose in a process that substitutes three hydroxyl groups by three chlorine atoms, resulting in a high intensity sweetener, approximately 600 times sweeter than sugar. For light and diet products the sucralose sweetener can be used either isolated or associated to other sweeteners. The most suitable technique for sucralose determination is the high performance liquid chromatography (HPLC) with refractive index detection. The present study aimed to use a technique recommended by Food Chemical Codex (FCC) and by JECFA (FAO/WHO) for analysis of pure sucralose in diet soft drinks and table top sweeteners samples. The employed technique was HPLC on a C-18 reverse-phase column, with a mobile phase water/acetonitrile (85:15 v/v), and refractive index detection; the external standard method was used for quantification. The obtained calibration curve was linear at 95 % confidence level with R2adjust = 1.00. The recoveries varied from 96 to 101 %. Sucralose concentrations ranged from 0.1 to 7 g. 100 g-1 for table top sweeteners, and from 6.1 to 16.2 mg. 100 mL-1 for soft drinks samples. The application of this methodology proved to be very efficient for processing the sucralose separation and its quantification in analyzed samples.